Long-term clinical and cost-effectiveness of collaborative care (versus usual care) for people with mental–physical multimorbidity: cluster-randomised trial. (15th May 2018) - Camacho, Elizabeth M.; Davies, Linda M.; Hann, Mark; Small, Nicola; Bower, Peter; Chew-Graham, Carolyn; Baguely, Clare; Gask, Linda; Dickens, Chris M.; Lovell, Karina; Waheed, Waquas; Gibbons, Chris J.; et al.
Abstract : Background: Collaborative care can support the treatment of depression in people with long-term conditions, but long-term benefits and costs are unknown. Aims: To explore the long-term (24-month) effectiveness and cost-effectiveness of collaborative care in people with mental-physical multimorbidity. Method: A cluster randomised trial compared collaborative care (integrated physical and mental healthcare) with usual care for depression alongside diabetes and/or coronary heart disease. Depression symptoms were measured by the symptom checklist-depression scale (SCL-D13). The economic evaluation was from the perspective of the English National Health Service. Results: 191 participants were allocated to collaborative care and 196 to usual care. At 24 months, the mean SCL-D13 score was 0.27 (95% CI, −0.48 to −0.06) lower in the collaborative care group alongside a gain of 0.14 (95% CI, 0.06-0.21) quality-adjusted life-years (QALYs). The cost per QALY gained was £13 069. Conclusions: In the long term, collaborative care reduces depression and is potentially cost-effective at internationally accepted willingness-to-pay thresholds. Declaration of interest: None.